2015
DOI: 10.1016/j.jmb.2015.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Negative Epistasis and Evolvability in TEM-1 β-Lactamase—The Thin Line between an Enzyme's Conformational Freedom and Disorder

Abstract: Epistasis is a key factor in evolution, since it determines which combinations of mutations provide adaptive solutions and which mutational pathways towards these solutions are accessible by natural selection. There is growing evidence for the pervasiveness of sign epistasis – a complete reversion of mutational effects, particularly in protein evolution, yet its molecular basis remains poorly understood. We describe the structural basis of sign epistasis between G238S and R164S, two adaptive mutations in the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
138
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(156 citation statements)
references
References 71 publications
9
138
3
Order By: Relevance
“…This hypothesis is supported by computational models and room temperature crystals that have revealed TEM adopts diverse structures11121314. A growing body of work argues for the importance of conformational heterogeneity in processes like allostery151617, ligand binding1819202122 and catalysis42324.…”
mentioning
confidence: 88%
“…This hypothesis is supported by computational models and room temperature crystals that have revealed TEM adopts diverse structures11121314. A growing body of work argues for the importance of conformational heterogeneity in processes like allostery151617, ligand binding1819202122 and catalysis42324.…”
mentioning
confidence: 88%
“…Studies have shown that these modifications effectively aid the enzyme resistance by expanding the active site cavity in order to either accommodate larger substrates or improve the formation of electrostatic bonds . Identifying the vast spectrum of structural motifs capable of holding this catalytic activity is therefore essential to understand the evolutionary capabilities of an enzyme and an important step toward the future design of clinically useful antibiotics and β‐lactamase inhibitors.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, Asn170 that coordinates the deacylating water molecule adopts a non--catalytic configuration, even when a covalent inhibitor occupies the active--site. The entropic cost of selecting from multiple sub--states, and foremost, the dominance of an impaired conformation of N170, underlie the very low catalytic efficiency of the double mutant(85).…”
mentioning
confidence: 99%